Perlindungan Gajah Sumatera di Aceh Berdasarkan Convention on Biological Diversity (CBD) 1992 - Crisdayanti Sutanto; Amalia Zuhra (Faculty of Law, Universitas Trisakti, 2023)
An animal bearing the designation of endangered species is the Sumatran elephant. These creatures' extinction is being brought on by the alteration of their environment for human usage. The formulation of the research's problem is whether or not the opening of land for oil palm plantations harms the habitat of Sumatran elephants in Aceh and what steps should be taken to protect them there in accordance with the Convention on Biological Diversity (CBD 1992). The government has implemented a variety of policies and oversees them with the help of the local community and other stakeholders